Implications of the Incidental Finding of a MYCN Amplified Adrenal Tumor: A Case Report and Update of a Pediatric Disease Diagnosed in Adults - Anna Koumarianou; Panagiota Oikonomopoulou; Margarita Baka; Dimitrios Vlachodimitropoulos; Stylianos Argentos; Theodoros Piperos; Maria-Ioanna Christodoulou; Kakoulis Theodoulou; Theodoros Mariolis-Sapsakos (Case Reports in Oncological Medicine)
MYCN is a well-known oncogene overexpressed in different human malignancies including neuroblastoma, rhabdomyosarcoma, medulloblastoma, astrocytoma, Wilms’ tumor, and small cell lung cancer. While neuroblastoma is one of the most common childhood malignancies, in adults it is extremely rare and its treatment is based on pediatric protocols that take into consideration stage and genotypic features, such as MYCN amplification. Although neuroblastoma therapy has evolved, identification of early stage patients who need chemotherapy continues to pose a therapeutic challenge. The emerging prognostic role of MYCN phenotype of this disease is currently under investigation as it may redefine MYCN amplified subgroups. We describe an unusual case of adult neuroblastoma with MYCN amplification diagnosed incidentally and discuss possible therapeutic dilemmas.